La mobilisation du développement durable dans les pratiques professionnelles des prestataires sportifs et touristiques - Clémence Perrin-Malterre (Développement Durable et Territoires)
The object of this article is to study the way of sports’ professionals mobilize the sustainable development in their professional practices. Through the concept of logics of action, we favor a comprehensive approach of individual trajectories. The comprehensive methodology rests on conversations with sports’ professionals. Results show an offer of soft practices centred on the discovery of the environment. Sports’ professionals want to share strong relational experiences with their customers. This moment of exchange is also a moment of transmission. Actors want to participate in the local development. We can show a territorial anchoring with an implication in associative and/or political activities of the territory.